Prospecting theoretical approaches to understand internationalization of creative economy firms - de Vasconcellos, Sílvio Luís; Monticelli, Jefferson Marlon; Calixto, Cyntia Vilasboas; Garrido, Ivan Lapuente (Internext, 2017)
We argue that the internationalization process of firms in the creative economy has particular aspects that distinguish it from internationalization of firms in traditional economic sectors. We explore ways in which the international business literature might be helpful for understanding how internationalization takes place in firms whose core business is creation of ideas. We conducted a case study using a focus group technique to investigate a creative economy firm specialized in computer graphics. The firm already does business internationally as a producer of electronic mockup models, but is transitioning to the computer-generated video production industry. Our results suggest that behavioral approaches to international business related to entrepreneurship, as well as country origin effects and networks theory could be useful to expanding knowledge about the internationalization process in such firms, in which creativity is a critical resource.